Optical thin films user handbook - Rancourt, James D. (SPIE Optical Engineering Press, 1996)
Practical, user-oriented reference for engineers who must incorporate and specify coatings for filters, antiglare effects, polarization, or other purposes in optical or electro-optical systems design. It focuses on preparation techniques and characteristics of commercially available products and provides information needed to determine what type of filter is needed to solve a particular problem, what its limitations are, and how to care for it.
Keywords: Optical coatings.; Thin films -- Optical properties.; Optical films.; Light filters.; elektronické knihy; electronic books